Enhancing the Policy Impact of African Research: Strategies for Visibility and Influence through Overton - Adie, Euan (My University, 2024)
Enhancing the Policy Impact of African Research: Strategies for Visibility and Influence through Overton - AfricArXiv Open Science Webinar Series 2024
This webinar session featured Euan Adie, the CEO of Overton. He spoke on the topic: Enhancing the Policy Impact of African Research: Strategies for Visibility and Influence through Overton African researchers and other attendees learned how to make their research more visible to policymakers and track its impact using Overton. They also got tips on engaging with policymakers and saw examples of how African research has influenced policy decisions. This webinar series is co-organized by: UbuntuNet Alliance: https://ubuntunet.net/ and Access 2 Perspectives: https://access2perspectives.org/ as part of the ORCID Global Participation Program: https://info.orcid.org/global-participation-program/
Keywords: Open Science; Open Access; Research; African Research; AfricArXiv; Overton; Policy Impact